Stability of gag-ca gene of Jembrana Virus in pcDNA-ca recombinant plasmid vector in Escherichia coli DH5α which has been stored for eight years - Baso Yusuf; Adyatma M Nur; Nur Fiska Yunitasari; Tri Ari Widiastuti; Endah Puspitasari (Jurnal Sain Veteriner, 2014)
The aim of this study was to determine the stability of gag-ca gene in a pcDNA-ca recombinant plasmid vector in Escherichia coli DH5α which has been stored for eight years using Polymerase Chain Reaction method (PCR). Gag-ca gene which codes mayor protein has been characterized as immunodominan antigen, and it also has positive reaction to animal antibody which infected by Jembrana virus, so it usually used as vaccine resources and serologic detection for Jembrana disease. The research was done by analyzing gag-ca gene of Jembrana virus in pcDNA-ca recombinant plasmid in Escherichia coli DH5α which has been stored for eightyears. The pcDNA-ca recombinant plasmid was purified from cultured Escherichia coli DH5α recombinant bacteria using "High Pure Plasmid Isolation Kit", then amplificated with “Pure Taq-Ready To Go PCR Kit” using specific primers. PCR products showed a positive result that pcDNA-ca recombinant plasmid contains gag-ca gene. PCR products identification using electrophoresis on agarose gel 1% showed that DNA stand apparently carried gag-ca gene at approximate amplicon 210 base pair (bp).